Maternal–Child Microbiome: Specimen Collection, Storage, and Implications for Research and Practice. Issue 2 (March 2017) - Jordan, Sheila; Baker, Brenda; Dunn, Alexis; Edwards, Sara; Ferranti, Erin; Mutic, Abby D.; Yang, Irene; Rodriguez, Jeannie
Abstract : Background: The maternal microbiome is a key contributor to the development and outcomes of pregnancy and the health status of both mother and infant. Significant advances are occurring in the science of the maternal and child microbiome and hold promise in improving outcomes related to pregnancy complications, child development, and chronic health conditions of mother and child. Objectives: The purpose of this study was to review site-specific considerations in the collection and storage of maternal and child microbiome samples and its implications for nursing research and practice. Approach: Microbiome sampling protocols were reviewed and synthesized. Precautions across sampling protocols were also noted. Results: Oral, vaginal, gut, placental, and breast milk are viable sources for sampling the maternal and/or child microbiome. Prior to sampling, special considerations need to be addressed related to various factors including current medications, health status, and hygiene practices. Proper storage of samples will avoid degradation of cellular and DNA structures vital for analysis. Discussion: Changes in the microbiome throughout the perinatal, postpartum, and childhood periods are dramatic and significant to outcomes of the pregnancy and the long-term health of mother and child. Proper sampling techniques are required to produce reliable results from which evidence-based practice recommendations will be built. Ethical and practical issues surrounding study design and protocol development must also be considered when researching vulnerable groups such as pregnant women and infants. Nurses hold the responsibility to both perform the research and to translate findings from microbiome investigations for clinical use.